Perancangan Produksi Video Dokumenter Merangkai Keindahan Menganyam Harapan Sebagai Media Promosi Kerajinan Rangkaian Bunga Nusantara - Kamilah, Eka Putri; Almanzhani, Shifa Amalia; Hanafi, Ardiansyah Rizal; Kurnia, Kurnia (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Weaving Beauty, Weaving Hope is the idea of a short documentary video work which is designed as a work object analyzed in depth to be able to communicate the meaning behind the creation of the flower arrangement. Based on these phenomena and problems, the aim of designing the documentary short video work Arranging the Beauty of Weaving Hope is to understand how to design a short documentary video production to promote the value of the product so that it can persuade consumer decisions. The project for making this work is a documentary video entitled